2015
DOI: 10.5455/ijmsph.2015.1211201470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood donor deferral causes: a tertiary-care center-based study

Abstract: According to the figures of World Health Organization (WHO), over 81 million units of blood are collected annually worldwide, but only 39% are collected in developing countries, which have 82% of the world's population. [2] A blood bank plays an important role in ensuring the supply of safe blood as and when required. Although it is important to ensure that there is an adequate supply of blood, it is also essential that the blood collection process does not harm either the donor or the recipient. This is achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 4 publications
13
15
0
Order By: Relevance
“…The donor deferral population was categorized into temporary and permanent deferrals. Among the deferrals, temporary causes (76.19%) were more common as compared to permanent causes (23.81%).The most common cause of temporary deferral in both males and females was anemia (46.5%) in our study which was similar with other previous studies [15,16] . This supports the fact that the prevalence of clinical and subclinical anemia is very high in developing countries like India.…”
Section: Discussionsupporting
confidence: 91%
“…The donor deferral population was categorized into temporary and permanent deferrals. Among the deferrals, temporary causes (76.19%) were more common as compared to permanent causes (23.81%).The most common cause of temporary deferral in both males and females was anemia (46.5%) in our study which was similar with other previous studies [15,16] . This supports the fact that the prevalence of clinical and subclinical anemia is very high in developing countries like India.…”
Section: Discussionsupporting
confidence: 91%
“…of male deferrals were much higher (72%) than female donors (21.73%). 11,12 It was observed in our study that prevalence of anemia is 2.3% in total blood donors (Table 3). Similar findings were shown by Bahadur et al and Kumari et al, who reported 1.8 % and 1.7% anemia, respectively in their studies.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies, as well as the present study, reveal that the most common cause of deferral is due to low hemoglobin concentration or anemia followed by low BP, animal bite, typhoid, menstrual cycle, body tattoo, underweight, antibiotic, thin vein, fast bleeding, and chikungunya. Anemia occurs due to improper dietary source and intake of junk food and snacks that lead to decreased nutrition level [10][11][12] were due to low hemoglobin concentration or anemia 13 . Anemia can be cured by taking proper treatment with regular checkups and awareness of dietary sources.…”
Section: Resultsmentioning
confidence: 99%